1993
DOI: 10.1073/pnas.90.14.6726
|View full text |Cite
|
Sign up to set email alerts
|

A Jun-binding protein related to a putative tumor suppressor.

Abstract: A lambda gt11 cDNA library of chicken embryo fibroblasts was screened with biotinylated Jun protein to identify Jun-binding clones. Eight such clones were isolated; one contains a gene referred to as jif-1 that is homologous to the putative tumor suppressor gene QM. jif-1 codes for a protein of 25 kDa that binds to the leucine zipper of viral and cellular Jun. The Jif-1 protein also binds to itself. Jif-1 does not contain a leucine zipper, and it does not bind to the 12-O-tetradecanoylphorbol 13-acetate respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 38 publications
1
76
0
2
Order By: Relevance
“…The findings that QSR1 homologues appear to be more highly expressed in undifferentiated mouse (6) and plant (8) cells are consistent with the fact that ribosomal genes are highly expressed in growing cells (29). In the cloning of jif-1, the chicken homologue of QSR1, it was found that Jif-1 interacts with c-Jun and that Jif-1 could disrupt Jun-Jun dimers (7). While it is conceivable that a cytoplasmic protein could translocate to the nucleus under some conditions and activate or repress transcription, it is also possible that the Jif-1/c-Jun interaction in vitro is a nonspecific interaction of the very basic Jif-1 with an acidic domain on c-Jun.…”
Section: Discussionmentioning
confidence: 55%
“…The findings that QSR1 homologues appear to be more highly expressed in undifferentiated mouse (6) and plant (8) cells are consistent with the fact that ribosomal genes are highly expressed in growing cells (29). In the cloning of jif-1, the chicken homologue of QSR1, it was found that Jif-1 interacts with c-Jun and that Jif-1 could disrupt Jun-Jun dimers (7). While it is conceivable that a cytoplasmic protein could translocate to the nucleus under some conditions and activate or repress transcription, it is also possible that the Jif-1/c-Jun interaction in vitro is a nonspecific interaction of the very basic Jif-1 with an acidic domain on c-Jun.…”
Section: Discussionmentioning
confidence: 55%
“…Although a participation of the other two RPL10 proteins, B and C, in translation under UV-B light was not demonstrated here, it is still possible that these proteins may have a role under different UV-B light conditions or under a different developmental stage. Some evidence indicates that RPL10/QM act as coactivators/repressors of transcription in human, Entamoeba histolytica, and chicken (Monteclaro and Vogt, 1993;Stanbridge et al, 1994;Chávez-Ríos et al, 2003). QM protein has also been shown to interact with the proto-oncogene c-Yes, a Src family kinase, and it can thus participate in signal transduction pathways in different intracellular processes, including cell stability, division, proliferation, migration, and differentiation (Oh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, human L10 was first identified as QM, a putative suppressor of Wilms' tumor (Dowdy et al, 1991). QM is highly homologous to the Jun-binding protein (Jif-1), a putative tumor suppressor; it has been reported that Jif-1 forms a complex with c-Jun and represses its ability to transactivate gene expression via inhibition of binding of c-Jun to DNA (Monteclaro and Vogt, 1993). Most QM proteins are localized in the cytoplasm, and subcellular fractionation assays have shown that QM is peripherally localized to the endoplasmic reticulum (Nguyen et al, 1998).…”
mentioning
confidence: 99%
“…These observations show an inverse correlation between QM levels and the differentiation status and are consistent with some early in vitro data suggesting QM protein as a putative tumor suppressor gene. 8,25 Thus, downregulation of QM may be associated with the development of prostate cancer in humans and may be used as a marker for early stage of prostate cancer. In this study, the expression of QM protein in prostate tumor cells did not correlate with the extra-prostatic extension or high tumor volume, but correlated with the low-grade prostatic adenocarcinoma (Gleason grade 3), and with the low percentages of the prostatic gland involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Both human QM and chicken homolog of QM/Jif-1 was reported to interact with the transcription factor c-Jun and thus inhibited cJun to activate genes containing AP-1 binding sites. 7,8 Although some investigators report that such interaction rarely occurs in vivo, 9 others further show that the interaction with c-Jun occurs via binding to the leucine zipper region of c-Jun, which is controlled by a protein kinase C phosphorylation event via zinc domain. 10 C-Jun and c-Fos are transcription factor subunits that bind as a homo or hetero-dimer complex to the AP-1 binding site in the promoter regions of many genes, especially those regulated by sex hormones.…”
Section: Introductionmentioning
confidence: 99%